Methods for Evaluating Sensory, Affective and Cognitive Disorders in Neuropathic Rodents - Palazzo, Enza; Marabese, Ida; Gargano, Francesca; Guida, Francesca; Belardo, Carmela; Maione, Sabatino (Current Neuropharmacology, 2021)
The animal models of neuropathic pain that faithfully reproduce the symptoms that occur in humans are a fundamental tool for understanding the mechanisms underlying the disease, identifying new targets, and developing effective drugs. So far, the studies aimed at describing the animal models of neuropathic pain have been focused mainly on the sensory symptoms associated with the disease consisting of mechanical allodynia and hyperalgesia, cold allodynia and hyperalgesia, and heat hyperalgesia. However, affective and cognitive comorbidities occur in patients suffering from neuropathic pain, arising in a closely associated and dependent manner on the sensory symptoms. The same occurs in animal models of neuropathic pain in which anxiety- and depressive- like behaviors and cognitive disorders are observable at different time points from the induction of neuropathy. Today there are several tests available that exploit different paradigms in rodents for measuring sensorial, affective, and cognitive behavior. This review will describe those mainly used in the scientific community. The tests mainly used are based on the motor activity of the animals tested, so it is fundamental that it remains unaffected in the model used for inducing neuropathic pain. We hope that this review will be useful to the scientific community to direct the choice towards the best, most suitable, and simplest tests for the study of the sensory, affective, and cognitive symptoms associated with neuropathic pain.
Keywords: anxiety-like and depression-like behavior